The impact of a ten-week physical exercise program on health-related quality of life in patients with inflammatory bowel disease: A prospective randomized controlled trial - Klare, Peter; Nigg, Johanna; Nold, Johannes; Haller, Bernhard; Krug, Anne B.; Mair, Sebastian; Thoeringer, Christoph K.; Christle, Jeffrey W.; Schmid, Roland M.; Halle, Martin; Huber, Wolfgang (Digestion, 2015)
Background: Improving health-related quality of life is a primary target of therapy for patients with inflammatory bowel disease. Physical activity has been demonstrated to improve health-related quality of life in several patient populations with chronic disease. There are very few studies investigating the effects of physical activity on health-related quality of life in inflammatory bowel disease. The primary purpose of this study is to investigate the effects of 10 weeks of moderate physical activity on health-related quality of life in patients with inflammatory bowel disease. Methods: Thirty patients with mild to moderate IBD (Crohn's Disease Activity Index (CDAI) <220 or Rachmilewitz Index (RI) <11) were randomized 1:1 to either supervised moderate-intensity running thrice a week for 10 weeks or a control group who were not prescribed any exercise. Health-related quality of life, symptoms, and inflammation were assessed at baseline and after 10 weeks. Results: Participants were 41 ± 14 years (73% female), had a body mass index of 22.8 ± 4.1 kg/m2, and an average CDAI or RI of 66.8 ± 42.4 and 3.6 ± 3.1. No adverse events occurred during the 10-week training period. Health-related quality of life, reported as IBDQ total score, improved 19% in the intervention group and 8% in the control group. Scores for the IBDQ social sub-scale were significantly improved in the intervention group compared with controls (ΔIBDQsocial = 6.27 ± 5.46 vs. 1.87 ± 4.76, p = 0.023). Conclusion: Patients suffering from moderately active IBD are capable of performing symptom-free regular endurance exercise. Our data support the assumption that PA is feasible in IBD patients. PA may furthermore improve quality of life through improvements in social well-being, and may, therefore, be a useful adjunct to IBD therapy.
CRIS-Team Scopus Importer:2023-03-08
Keywords: HRQOL; IBD; Physical activity; Physical exercise